(untitled) (International Association of Biologicals and Computational Digest, 2022)
Image Colorization is the process of adding colors to monochrome, grayscale or sepia images. There are several different methods of colorization. From that we have studied two algorithms which gives exceptionally promising outcomes. The goal of this paper is to implement existing algorithms to color a grayscale image. so, we are going to implement following algorithms in our paper: • optimization-based coloring, in which artist have to annotate image using color it is proposed by Levin et al. [3]. It is based on simple idea “neighbouring pixels in space-time that have similar intensities should have similar colors”. • Pseudo Coloring, a method of assigning arbitrary colors with the help of colormap (Look-Up table).